Surgery in the Theresienstadt Jewish ghetto - Horáčková, Kateřina; Grymová, Renáta; Hrstka, Zdeněk; Moravcová, Markéta; Ševčovičová, Andrea; Pilný, Jaroslav; Děrňarová, Lubica (My University, 2020)
BACKGROUND: The aim of this study is to identify the most common types of surgical interventions performed at the Theresienstadt ghetto in its period. The aim is also to determine the most common medical diagnoses leading to surgical interventions, and to identify the most active operating surgeons. METHODS: The data was obtained from valid primary and secondary sources of the highest importance (archival material, transcribed memoirs, monographs and articles). The main source of data was the Surgical Logbook (Theresienstadt Memorial Archive, No. 9105) dating from November 1944 to June 1945, which defined the data collection period. In order to obtain relevant results, an adequate source criticism was followed by the analysis of the content of the valid data, which became a foundation for a historical case study. RESULTS: The analysis of the data recorded in the Surgical Logbook focused on types of surgical interventions, diagnoses and types of anaesthesia used. In the observed period, the most common interventions were surgical (325), gynaecological (39) and urological (36). The most common medical diagnoses that led to surgery included abscess, phlegmon, inguinal hernia, uterine fibroids, prostatic hyperplasia and breast cancer. Most surgical procedures were performed in general anaesthesia using Ether and Epivan. The most active surgeons were Dr. Springer, Dr. Braun and Dr. Klein. CONCLUSIONS: The article represents a unique historical research filling the gaps in Holocaust research. Conclusions give a real picture of surgical care in the Theresienstadt ghetto at the end of World War II.
Chirurgie v ghettu Terezín
Keywords: poverty areas; Holocaust; surgery; oblasti chudoby; holokaust; chirurgie